Fundamentals of Entrepreneurship (ENT300) : Edens of Chocolate / Nur Astati Sahari … [et al.] - Sahari, Nur Astati; Hasli, Wanaatashia Najeera; Tinggom, Raymond Hollis; Jubin, Liliana Jessy; Stephanie, Stephanie (2013)
Our company name is Edens of Chocolate. The business has been decided on the form of partnership, which consist of five members. Each partner contributes certain amount of capital as agreed in our agreement. Our main business activity is to provide a one stop restaurant where all chocolate lover may experience a memorable unique and tasty chocolate rich dipping with fruits, cakes, biscuits or ice cream. We have decided that our business will operate at The Spring Shopping mall, Kuching, Sarawak. It will fully operate on I st January 2013. All partners are encourage and entitled to participate in the business management. We have agreed that Nur Astati Binti Sahari as the General Manager, Wanaatashia Najeerah Binti Hasli will be our Administrative Manager, while Raymond Hollis ak Tinggom will act as our Marketing Manager, Liliana Jessy ak Jubin will hold the post of Operation Manager, and also Stephanie ak Pilipin had been appointed as our Financial Manager.